ROCK-nmMyoII, Notch and Neurog3 gene-dosage link epithelial morphogenesis with cell fate in the pancreatic endocrine-progenitor niche - Bankaitis, Eric D. (Development, 2018)
During mouse pancreas organogenesis, endocrine cells are born from progenitors residing in an epithelial plexus niche. After a period in a lineage-primed Neurog3(LO) state, progenitors become endocrine committed via upregulation of Neurog3. We find that the Neurog3(LO) to Neurog3(HI) transition is associated with distinct stages of an epithelial egression process: narrowing the apical surface of the cell, basalward cell movement and eventual cell-rear detachment from the apical lumen surface to allow clustering as nascent islets under the basement membrane. Apical narrowing, basalward movement and Neurog3 transcriptional upregulation still occur without Neurog3 protein, suggesting that morphogenetic cues deployed within the plexus initiate endocrine commitment upstream or independently of Neurog3. Neurog3 is required for cell-rear detachment and complete endocrine-cell birth. The ROCK-nmMyoII pathway coordinates epithelial-cell morphogenesis and the progression through Neurog3-expressing states. NmMyoII is necessary for apical narrowing, basalward cell displacement and Neurog3 upregulation, but all three are limited by ROCK activity. We propose that ROCK-nmMyoII activity, Neurog3 gene-dose and Notch signaling integrate endocrine fate allocation with epithelial plexus growth and morphogenesis, representing a feedback control circuit that coordinates morphogenesis with lineage diversification in the endocrine-birth niche.